The Role of Saudi Law in Regulating Digital Media and Combating Misleading Propaganda (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to reveal the role of Saudi law in regulating digital media and combating misleading propaganda in the Kingdom of Saudi Arabia. The study relied on the descriptive analytical approach. Data were collected through an electronic questionnaire that included 377 lawyers and media professionals in the Kingdom of Saudi Arabia, who were selected by simple random sampling. Descriptive and inferential statistical tests were used to analyze the data, such as mean, standard deviation, regression analysis, and correlation analysis. The results of the study showed a statistically significant positive relationship between the role of media professionals and lawyers in combating misleading propaganda and the effectiveness of Saudi law in this field. The results also showed that the role of media professionals and lawyers positively affects the clarity, strength, and application of the law. Based on these results, the study recommended the necessity of enhancing cooperation between media professionals and lawyers, developing awareness and training programs, reviewing laws and regulations, and encouraging scientific research in this field.
Keywords: Saudi Law; Digital Media; Misleading Propaganda; Media Regulation; Combating Misinformation; Media Awareness; Media Practices; Role of Lawyers